Mechanical, Chemical and Microstructure Properties of Composite Edible Film Added with Modified Casein - Mulia W. Apriliyani, MP; Ria Dewi Andriani; Premy Puspitawati Rahayu; Purwadi Purwadi; Abdul Manab (Faculty of Animal Science Universitas Brawijaya, 2020)
Edible film is potentially applied to replace non-biodegradable packaging for animal products, e.g. meat and meat products. The overall objective of this study was to observe the effect of different addition levels of modified casein hydrolysate (casein-catechin complexes) on mechanical (film thickness, water vapor permeability, tensile strength, elasticity), chemical (moisture content, water activity, and solubility) and microstructure properties of composite edible casein film. The edible films were formulated according to different combinations of modified casein hydrolysate and casein film solution (0.50:0.25, 0.50:0.50, 0.75:0.25, and 0.75:0.50) and compared with control (without addition of modified casein). No significant effects of the treatment were found on film thickness, water vapor permeability, tensile strength, elasticity, moisture content, water activity, and solubility of the composite edible film. However, the micrographs show that the amount of polymer was higher as the proportion of catechin was increased. In conclusion, the addition of catechin-added casein (modified casein) to casein edible film solution at up to 0.5% did not alter the mechanical properties, moisture content, water activity and solubility of the composite edible film.